Monolithic integration of metastable α-In2Se3 thin film on H-passivated Si(1 1 1) for photovoltaic applications. (10th March 2016) - Li, Handong; Ren, Wuyang; Wang, Gaoyun; Gao, Lei; Peng, Ruoming; Li, Hui; Zhang, Pingyi; Shafa, Muhammad; Tong, Xin; Luo, Siyuan; Zhou, Zhihua; Ji, Haining; et al.
Abstract: The metastable α -In2 Se3 thin film is epitaxially integrated on H-passivated Si (1 1 1) substrates to build a novel heterojunction solar cell by molecular beam epitaxy. The growth of In2 Se3 on H–Si(1 1 1) at low temperature initiates as an amorphous layer then followed by re-crystalline of α phase film. Electronic transport properties of α -In2 Se3 /p-Si heterostructure are studied. Analysis of the temperature dependence of thermionic emission in reverse bias indicates a barrier height of ~0.21 eV at the α -In2 Se3 /p-Si interface. A photovoltaic conversion efficiency of 2% is measured for the heterojunction with optimized In2 Se3 film thickness.